Analisis Efek Samping Penggunaan Vaksin COVID-19 (Booster) Moderna COVID19 VaccineÂ® Pada Tenaga Kesehatan Di Puskesmas Santong, Kecamatan Kayangan, Kabupaten Lombok Utara Tahun 2023 - Mulianti, Handini; Zuhri, Muhammad Isnaini; Isasih, Widani Darma (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2023)
The Coronavirus Disease 2019 (COVID-19) is an infectious condition caused by the SARS-CoV-2 virus. This virus has undergone mutations, leading to new variants that have contributed to the increase in COVID-19 cases. Governments have initiated vaccination efforts as part of their strategies to curb the spread, particularly among healthcare workers. However, concerns have arisen regarding the occurrence of post-vaccination side effects. The objective of this study is to identify and categorize the side effects that arise after administering the COVID-19 (booster) vaccine, specifically the Moderna COVID-19 VaccineÂ®. The study employs a cross-sectional approach, collecting data through interviews and questionnaire completion among medical staff at Puskesmas Santong in April 2023. The study's findings reveal that out of 69 respondents, 94.2% experienced side effects following vaccination, while 5.8% did not encounter any. The majority of these side effects fall into the "probable" category (69.6%) according to the Naranjo Scale Algorithm. Common systemic side effects include fever (60.9%), dizziness (43.5%), fatigue (33.3%), muscle aches (31.9%), joint pain (13%), chills (11.6%), headache (10.1%), nausea (4.3%), runny nose (1.4%), and sneezing (1.4%). Local side effects, such as injection site pain, were reported by 34.8% of the respondents. The majority of these side effects persisted for 2 days (42%).